(untitled) (Proceedings of Southern Federal University. Philology, 2017)
Alexandra V. Butenko (Veliky Novgorod, Russian Federation) The article discusses the concept of «Chechen text», which represents the local supratext, formed as a result of the literary and journalistic reflection events of the first and second Chechen campaign (1994-1996s, 1999-2009s). V.N.Toporov’s discovery of the Petersburg Text of Russian literature led to the idea of extrapolating of the supratext on other culturally significant loci. The article notes that the mythology and liminality are important features of the supratext, and its integrity forms common elements: the space-time organization, landscape description, through motives. One of these motives is the motive of the mirror, which functions in accordance with the tradition mythopoetic, indicating the border. Crossing through the mirror facet, due to the literary texts by G.Sadulaev, Z.Prilepin, A.Prokhanov symbolizes the immersion in a surreal hostile space, the space of war and violence. The image of a cloudy broken mirror, manifested in the story by P.Zherebtsova «Little angel», is interpreted as a sign of universal misery, destruction of the fundamental laws of life. The article deals with options such as complex semantic mirror, like a bridge, and glass. The implementation of the principle of the mirror vision (analogue mirror – dream) may be the subject of a separate study. Key words: military prose of the 2000s, supratext, mirror motive, Chechen text.